Theoretical Study on Self-Organization of Vegetation Patterns Triggered by Water Resource in Deposited Sediment Layer - Tousheng Huang; Huayong Zhang; Zhao Liu; Ge Pan; Xiumin Zhang; Zichun Gao (Complexity)
This research focuses on the self-organization of vegetation patterns on severely degraded eroding lands, triggered by water resource in the deposited sediment layer on which the vegetation patterns are formed. A nonlinear spatiotemporal model is developed with the consideration of the interactions between vegetation biomass and water resource stored in the sediment layer. With employment of the model, the conditions for pattern formation of the considered ecological system are determined via Turing instability analysis. Numerical simulations of the research demonstrate the formation of banded, labyrinth, and gapped vegetation patterns, with the parameter values taken from the literature. The characteristics of the vegetation patterns are analyzed. Comparing the characteristics of the vegetation patterns of this research with that available in literature, great similarity of pattern formation is shown. The results obtained provide a theoretical comprehension on natural vegetation restoration of severely degraded eroding lands.